Studi Eksperimental Pengaruh Perlakuan Alkali terhadap Kekuatan Tarik Serat Tunggal dan Ketahanan Robek Kain Tenun Serat Daun Nanas - Badri, Muftil; Silaban, Vrengky Roberto; Dalil, Mohammad (Rekayasa Material, Manufaktur dan Energi, 2026)
The tensile strength and tear resistance properties of pineapple leaf fiber can be improved as a new woven fabric product. This paper aims to experimentally investigate the effect of variations in alkali treatment using sodium hydroxide on the tensile strength of single fibers and tear strength of pineapple leaf fiber woven fabrics.  Alkaline treatment was carried out with variations in sodium hydroxide concentration of 2%, 4%, 8%, 10% and non-alkaline. Alkali treatment on single pineapple leaf fibers affected the tensile strength. The results showed that single pineapple leaf fibers non-alkali treatment had a tensile strength value of 80 N/mm2 and the alkali treatment with a percentage of 8% had the highest tensile strength of 108.57 N/mm2. Alkali treatment on pineapple leaf fibers affects the tear force of woven fabrics made from pineapple leaf fibers. The results showed that non-alkali-treated woven fabrics had a tear force of 47.40 N and the alkali treatment with a percentage of 8% experienced the highest force of 53.98 N. Single pineapple leaf fibers with 8% alkali treatment contained 87.78% cellulose. This shows that the effect of alkali on pineapple leaf fibers can increase the percentage of cellulose, resulting in higher mechanical properties of the fiber. At an alkali percentage of 10%, mechanical properties decreased.